ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIER MAHASISWA AKUNTANSI SEBAGAI AUDITOR - Irman, Mimelientesa; silvi, silvi (Research in Accounting Journal (RAJ), 2020)
The aims of this research is to determine and analysis factors of influence selection of career accounting student as an auditors. The factors is the financial rewards, professional training, work environment, market considerations and social values. The populations of this research is accounting student from the College of Economics Pelita Indonesia in Pekanbaru City. The samples in this research is 43 respondents. Method of collection data with using questionnaire, and data analysis is using multiple linier regression analysis with SPSS version 19. In this research a result is variable of the financial rewards, professional training, work environment, market considerations and social values not have an infuence on selection of career accounting student as an auditors.